IPTEKS PENGENDALIAN INTERN TERHADAP ASET TETAP DAN PERSEDIAAN DI KANTOR OTORITAS JASA KEUANGAN / KOJK PROVINSI SULAWESI UTARA, GORONTALO DAN MALUKU UTARA - Nani, Siti Sakina; Pangemanan, Sifrid S. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Otoritas Jasa Keuangan (OJK) is independent institution that performs duties and function of supervision in financial sector industry. This institution also does not escape from the use of fixed assets and inventories. The procurement of fixed assets depends on a certain nominal with recognition based on a positive list in accordance with the internal provisions applicable in the OJK. Internal control in the management of fixed assets and inventory is needed, so as to encourage the productivity of the operational performance of the OJK. Based on the research that has been done, internal control will run effectively and efficiently if it refers to the points in coco internal control, namely objectives, commitment, capability and supervision and learning. The results of this study are suggested to use the FIFO method in terms of structuring inventory so that the possibility of non-use / damaged goods becomes smaller.